206k views
10 votes
Y-b=m(x-a) solve for m

2 Answers

5 votes

Answer:

Explanation:

To solve y-b=m(x-a) for m, divide both sides of this equation by (x - a):

y - b

m = ---------------

(x - a)

User Rohit Shinde
by
6.2k points
4 votes

Answer:


m=(y-b)/(x-a)

Explanation:

Considering no values were supplied, the most we can do here is rearrange the equation to get m on its own.

In the equation y - b = m(x - a), since (x - a) is multiplicative of m, we can divide this value to remove it from m's side. This leaves us with:


m=(y-b)/(x-a)

User SzB
by
5.6k points